Theocratic Democracy: The Social Construction of Religious and Secular Extremism - Fatih Varol (Türkiye Ortadoğu Çalışmaları Dergisi, 2017)
Kitap Değerlendirmesi: Theocratic Democracy: The Social Construction of Religious and Secular Extremism